CLASSIFICATION OF HORIZONTAL AND VERTICAL CHANNELS OF SOCIAL MOBILITY THAT ENSURE THE SOCIAL ACTIVITY OF WOMEN IN MODERN SOCIETIES (Innovate Conferences, 2025)
In recent decades, the concept of social mobility has gained prominence in the discourse surrounding gender equality, empowerment, and inclusive development. Social mobility, broadly defined as the movement of individuals or groups within a social hierarchy, reflects both personal effort and structural opportunities. For women, especially those in patriarchal or resource-constrained societies, social mobility represents a gateway to active participation in public life, professional advancement, and civic engagement.